Takaful: a review on performance, issues and challenges in Malaysia - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Hasan, Sharina Farihah; Aripin, Srazali; Arifin, Muhammad Ariffuddin (University of Lagos, Nigeria, 2016)
This paper aims to bring to attention the state of takaful or Shariah compliant insurance industry in Malaysia. It provides a review on takaful and its performance in Malaysia and highlights issues and challenges it faced. The review is undertaken through a detail desk study. The outcome of the review suggests that the penetration growth of takaful in Malaysia is relatively small in contrast to the conventional insurance, and that the takaful industry faces a series of constraints that require immediate attention if the industry is going to offer a reliable alternative to conventional insurance.